(untitled) (Revista Brasileira de Plantas Medicinais, 2025)
This study aimed to determine the proximal and mineral composition of the unconventional food plants tupinambor (Helianthus tuberosus), ora-pro-nobis (Pereskia aculeata Miller) and moringa (Moringa oleifera Lam), commercialized as flour in the city of Porto Belo – SC. Proximal composition was determined according to the Association of Official Analytical Chemists and the concentration of minerals Fe, Cu, Zn, P, Ca and Mg by atomic absorption spectrometry and K by flame photometry. The results obtained were: moisture (0.88, 0.88 and 0.86 g 100 g-1), ash (16.34, 7.75 and 5.07 g 100 g-1), lipids (3.27, 5.57 and 0.48 g 100 g-1), protein (22.41, 24.79 and 6.53 g 100 g-1), carbohydrates (57.10, 62.02 and 87.06 g 100 g-1) e food fiber (55.39, 48.21 and 19.68 g 100 g-1). According to ANVISA Ordinance n°27, moringa and ora-pro-nobis flours present high protein content and all evaluated flours have high food fiber content. The average results obtained indicate that, except for iron, all samples show significant differences (p<0.05) in relation to the minerals concentration and with the exception of ora-pro-nobis flour that obtained higher calcium content, potassium was the mineral that obtained higher concentrations in the evaluated flours. According the RDC n°269 from ANVISA, the evaluated flours can be considered minerals sources; thus tupinambor flour a source of Ca and Mg, ora-pro-nobis flour of P, Ca and Mg and moringa flour of Ca and P. Finally, according to the Dietary Reference Intakes (DRIs), all the evaluated flours are K sources.